Multiple Pounding Tuned Mass Damper (MPTMD) control on benchmark tower subjected to earthquake excitations - Lin, W.; Lin, Y.; Song, G.; Li, Jun (2016)
To explore the application of traditional tuned mass dampers (TMDs) to the earthquake induced vibration control problem, a pounding tuned mass damper (PTMD) is proposed by adding a viscoelastic limitation to the traditional TMD. In the proposed PTMD, the vibration energy can be further dissipated through the impact between the attached mass and the viscoelastic layer. More energy dissipation modes can guarantee better control effectiveness under a suite of excitations. To further reduce mass ratio and enhance the implementation of the PTMD control, multiple PTMDs (MPTMD) control is then presented. After the experimental validation of the proposed improved Hertz based pounding model, the basic equations of the MPTMD controlled system are obtained. Numerical simulation is conducted on the benchmark model of the Canton Tower. The control effectiveness of the PTMD and the MPTMD is analyzed and compared under different earthquake inputs. The sensitivity and the optimization of the design parameters are also investigated. It is demonstrated that PTMDs have better control efficiency over the traditional TMDs, especially under more severe excitation. The control performance can be further improved with MPTMD control. The robustness can be enhanced while the attached mass for each PTMD can be greatly reduced. It is also demonstrated through the simulation that a non-uniformly distributed MPTMD has better control performance than the uniformly distributed one. Parameter study is carried out for both the PTMD and the MPTMD systems. Finally, the optimization of the design parameters, including mass ratio, initial gap value, and number of PTMD in the MPTMD system, is performed for control improvement.